2011
DOI: 10.1021/bi2003668
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Streptomyces coelicolor Phosphopantetheinyl Transferase, AcpS, Reveals the Basis for Relaxed Substrate Specificity

Abstract: The transfer of the phosphopantetheine chain from coenzyme A (CoA) to the acyl carrier protein (ACP), a key protein in both fatty acid and polyketide synthesis, is catalyzed by ACP synthase (AcpS). Streptomyces coelicolor AcpS is a doubly promiscuous enzyme capable of activation of ACPs from both fatty acid and polyketide synthesis and catalyzes the transfer of modified CoA substrates. Five crystal structures have been determined, including those of ligand-free AcpS, complexes with CoA and acetyl-CoA, and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
(106 reference statements)
0
23
1
1
Order By: Relevance
“…Arginine clusters are involved in binding of phosphate-containing molecules such as nucleotides, NADP, FMN, FAD and acetyl-CoA. 4648 Moreover, arginine clusters play a crucial role in stabilizing the propionic acid side chains of heme groups and bind frequently to organic acids and negatively charged bioactive compunds. 49,50 Finally, we found a number of arginine clusters stabilized by chlorides, sulfates, phosphates, acids and other molecules commonly present in the buffers used for protein purification and crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Arginine clusters are involved in binding of phosphate-containing molecules such as nucleotides, NADP, FMN, FAD and acetyl-CoA. 4648 Moreover, arginine clusters play a crucial role in stabilizing the propionic acid side chains of heme groups and bind frequently to organic acids and negatively charged bioactive compunds. 49,50 Finally, we found a number of arginine clusters stabilized by chlorides, sulfates, phosphates, acids and other molecules commonly present in the buffers used for protein purification and crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…The source of 4′PP for the transferase is CoA, but the enzyme can also use different acylated derivatives of CoA (Fig. 1b) (Dall’Aglio et al 2011). Indeed, it is often the case, since most of the CoA molecules in the cell are in the acylated form (Vallari et al 1987).…”
Section: Functions Of Teiismentioning
confidence: 99%
“…The crystal structure of Sfp and the studied protein complex with PCP revealed that Sfp has a pseudo-homodimeric fold and provides one V-shaped interface for the 4′-PP cofactor modification of a PCP (Figure 2c); in comparison AcpS is crystallized as a symmetric homo-trimer and three catalytic sites for the post-translational modification of ACPs are located in the interface of AcpS monomers (Figure 2d). 145-147 ACPs and PCPs had been shown to comprise of a three to four helix bundle, whereas the third helix is described as a short α- or 3 10 - helix. However, X-ray studies did not deal with the structural flexibility and dynamics, essential for the function of carrier proteins to shuttle to, interact with, and present their tethered, growing acyl chain to every catalytic domain in any NRPS/PKS/FAS module.…”
Section: A Peptidyl Carrier Protein-centered View Of Nrps Assemblymentioning
confidence: 99%